Impacts of Climate Change on the Livelihoods of Local People: A Case from Jethal V.D.C., Sindhupal-Chowk District - Nepali, Kul Bahadur; Pant, Ramesh Raj; Pradhanang, Sadhana (Crossing the Border: International Journal of Interdisciplinary Studies, 2014)
Abstract not available DOI: http://dx.doi.org/10.3126/ctbijis.v2i1.10820 Crossing the Border: International Journal of Interdisciplinary Studies Vol.2(1) 2014: 147-158